THE STATE OF CPR KNOWLEDGE: AN EVALUATION OF IRAQI NURSES - Hussein Abdulmohsin Dabis; Ali Talib Hameed (Western European Studies, 2024)
The generally known cardiopulmonary resuscitation (CPR) is the must-have qualification for any healthcare worker, with a specific focus being made on the nurses. But evidences implies that CPR information among nurses, especially in developing-world environments, may be limited. This research seeks to assess the knowledge on CPR and demographic characteristics of the nurses in Al-Nasiriyah Teaching Hospital, Thi-Qar, Iraq. Cross-sectional descriptive design was applied in this study to determine knowledge of CPR in 200 nurses of Al-Nasiriyah Teaching Hospital in Thi-Qar, Iraq via convenience sampling. Questionnaires developed by the researcher including socio-demographic questions and 20 multiple choice CPR knowledge questions were employed in the study. Quantitative data analysis included Descriptive statistics and multiple regression analysis were used during study. The necessary permissions were consequently sought and granted from the Thi-Qar health directorate while intact consent was also obtained from each participant while ensuring anonymity and privacy of data collected.
Keywords: privacy; ensuring; anonymity